Hegel and Kant on rational willing: The relevance of method*. Issue 2 (21st July 2014) - Stein, Sebastian
Abstract: Hegel's account of rational willing has recently been misrepresented by both critics and supporters who argue that the content of willing is externally received from history, social context, practices of recognition, etc. This contradicts the conceptual structure of Hegel's notion of rational action as free individuality, according to which the difference between the willing subject and the content of willing is an internal relation of identity. Since this 'difference within identity' can only be grasped by speculative thinking and not through understanding and reflection, the interpreters can be charged with employing the wrong method. Although reliance on the speculative method opens Hegel to the charge of unintelligibility, it helps explain the frequent misrepresentations of his account of freedom and why methodologically uninformed comparisons between Hegel and other thinkers run the risk of being counterproductive.